Copyright, Censorship And Ex Turpi Causa - Sethu, R.R. (Journal of Malaysian and Comparative Law, 2019)
The doctrine of binding precedents has no application to judgments at first instance. One High Court judge is not bound by the judgment of another. However, such decisions are followed as a matter of judicial courtesy. There are some instances both in England and Malaysia where one High Court refused to followed another. However, if a High Court has refused to follow an earlier High Court decision after referring to it, subsequent judges have the follow the later decision and not the earlier one unless the third judge is convinced that the second decision was wrong, e.g. some binding or persuasive authority had not been referred. Third judges have no general right to review.